A surface fluorination strategy to produce Zn anode for the 3D printable aqueous Zn batteries. (2022) - Li, Tian Chen; Lin, Congjian; Luo, Min; Li, Xue Liang; Li, Yifan; Yang, Hui Ying
Abstract: Despite many performance merits (e.g., high theoretical capacity, suitable redox potential, high natural abundance), the application of Zn metal anode is compromised by severe parasitic reactions and Zn dendrite growth in aqueous electrolytes. Herein, we proposed a modified Zn foil with zinc fluoride (ZnF2 ) surface layer deposited by a simple fluorination process. Fast ion diffusion kinetics, low nucleation overpotential contributes to uniform nucleation sites and dendrite-free Zn deposition. Meanwhile, due to the block effect, detrimental side reactions are also effectively mitigated. As a result, ZnF2 @Zn anode exhibits reversible Zn plating/stripping (700 h at 1 mA cm −2 ) with ultra-low voltage hysteresis (44 mV), leading to exceptional cycling stability over 300 cycles with 95.1 % capacity retention for the ZnF2 @Zn/MnO2 full cell. In addition, we have also explored a separate process to produce 3D printable cathode to pair with the Zn anode for a Zn-ion battery. The exploring of 3D printing method is of great importance for the industrial level of manufacturing of batteries, which are the bridge to transfer electrode materials to devices. The printed cathode will be used to demonstrate the fast prototype process.